Reconstructing Islamic Identity in Modern Times: A Narrative Review of Educational Reform and Intellectual Responses - Rahman, Gohar (Yayasan Sinergi Kawula Muda, 2025)
This study offers a comprehensive narrative review of the evolving relationship between Islamic philosophy and Western modernity. It aims to explore how Muslim intellectuals respond to the challenges of modern epistemology and secularism by reinterpreting classical Islamic concepts. The review applies a structured methodology involving major academic databases such as Scopus, PubMed, and Google Scholar, employing keywords like